2020
DOI: 10.1259/bjr.20190605
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of geriatrics index of comorbidity and MDCT findings for predicting mortality in patients with acute mesenteric ischemia due to superior mesenteric artery thromboembolism

Abstract: Objectives: To identify risk factors of geriatrics index of comorbidity (GIC) and multidetector CT (MDCT) findings for predicting mortality in patients with acute mesenteric ischemia (AMI) due to superior mesenteric artery (SMA) thromboembolism. Methods: 33 patients with AMI due to SMA thromboembolism underwent abdominal MDCT and angiography. Patients’ comorbidities and MDCT findings of ischemic bowel/mesenteric injuries, regions of SMA involved by thromboembolism, and degrees of SMA stenosis were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Sixty-one studies addressed the short-term mortality of occlusive arterial AMI 6 22 25 27 31–35 38 39 42 48 49 59 62 63 66 94 95 97 113–153. Meta-analysis showed an overall mortality of 51.8% (95% CI 46.3 to 57.3) (online supplemental figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-one studies addressed the short-term mortality of occlusive arterial AMI 6 22 25 27 31–35 38 39 42 48 49 59 62 63 66 94 95 97 113–153. Meta-analysis showed an overall mortality of 51.8% (95% CI 46.3 to 57.3) (online supplemental figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Even in institutions with enhanced CT, doctors will only consider utilizing it after an abnormal result of an unenhanced CT. Nuzzo, A et al reported that unenhanced CT was an independent risk factor associated with delayed diagnosis of AMI [35]. Decreased intestinal wall enhancement, pneumatosis intestinalis, mesenteric stranding, dilated bowel and ascites were reported in CTA with intestinal necrosis [9,11,12,36]. Mothes, H. et al reported that the speci city of pneumatosis intestinalis, decreased intestinal wall enhancement, and mesenteric stranding in predicting intestinal necrosis were 98.6%, 88.6% and 77.1%, respectively [9].…”
Section: Resultsmentioning
confidence: 99%
“… Notes that patients requiring antibiotic therapy were at significantly increased risk of death. Risk factors of geriatrics index of comorbidity and MDCT findings for predicting mortality in patients with acute mesenteric ischemia due to superior mesenteric artery thromboembolism [ 57 ] 2020 2013–2018 Retrospective Single Institution 33 Not mentioned. None Interdisciplinary approach in emergency revascularization and treatment for acute mesenteric ischemia [ 44 ] 2021 2010–2017 Prospective Single Institution 26 Not mentioned.…”
Section: Conclusion and A Call To Actionmentioning
confidence: 99%